Theoretical foundations of the development of oral and written language culture skills of primary school students - Aksionova V. V. (Education and science in the modern context, 2021)
This article examines the functioning of the Russian language in the form of oral and written speech. Both of these speech forms use the same units of language, but in different ways. Oral speech and written speech are designed for different perception and therefore differ in lexical composition and syntactic constructions.
Keywords: письменная речь; устная речь; written speech; oral speech; речевые формы; speech forms